2022
DOI: 10.3390/socsci11110509
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Creative Self-Efficacy, Achievement Motivation, and Job Burnout among Designers in China’s e-Market

Abstract: The e-market is prosperous in China, but the factors that stimulate or deter its development remain unclear. This study focuses on designers (interaction, user interface, product, and user experience designers) in the Chinese e-marketplace to examine the relationship between creative self-efficacy (CSE), achievement motivation (including motivation to approach success [MS], and motivation to avoid failure [MF]), and job burnout. Eighty-two questionnaires and eight in-depth interviews were used to collect data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…MCT has been a subject of growing interest and has received significant research attention (Liu et al, 2021;Power, 2015;Suherman & Vidákovich, 2022b; R.-N. Wang & Chang, 2022;Wu et al, 2022). These factors include ethnomathematics, parents' educational level, ATM, ethnic identity, and creative style.…”
Section: Mct and Ethnomathematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…MCT has been a subject of growing interest and has received significant research attention (Liu et al, 2021;Power, 2015;Suherman & Vidákovich, 2022b; R.-N. Wang & Chang, 2022;Wu et al, 2022). These factors include ethnomathematics, parents' educational level, ATM, ethnic identity, and creative style.…”
Section: Mct and Ethnomathematicsmentioning
confidence: 99%
“…Hence, MCT is not only an academic pursuit but also a means of strengthening students' affiliation with their ethnicity and culture (Soler Pastor et al, 2022;Tidikis et al, 2018). Despite these insights, the factors influencing student creativity, particularly in mathematics, remain unclear (Liu et al, 2021;Power, 2015;RN Wang & Chang, 2022;Wu et al, 2022). Understanding these factors, especially within the context of mathematics and culture (i.e., ethnomathematics), becomes crucial in devising effective educational strategies and fostering students' intellectual growth.…”
Section: Introductionmentioning
confidence: 99%
“…This convenience factor is related to how operational transactions are done online. According to Park and Yoon, Internet shopping allows customers to save their time and effort when buying the desired product (Khoa & Huynh, 2023;Wu et al, 2022).According (Kannan & Li, 2017) suggested that the advantages from the online consumer side, is one of convenience. With an online business, consumers no longer need to think about and experience traffic conditions, there is no need to think about parking, therefore consumer have more time to spend on product research, comparing prices, and ultimately buying products.…”
Section: Conveniencementioning
confidence: 99%
“…The existence of online buying and selling sites and applications such as Tokopedia, Bukalapak, Online shopping and Lazada allows us to be able to buy or sell goods without having to have an physical store.In the past, if we wanted to shop, we had to go somewhere to get the product we wanted. Now, we can order food, drinks, transportation, or hotels just by using our smartphones anytime and anywhere, as well as buying and selling goods (Wu et al, 2022). We simply choose the items we want to buy, then make payments, either by transferring funds to the seller via ATM (Automated Teller Machine), cutting off customer credit, COD (Cash On Delivery), or for those who shop through Online shopping, you can use Online shopping pay.…”
Section: Introductionmentioning
confidence: 99%